Non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio associated with psoriasis: a cross-sectional study - Liu, Xinyan; Li, Keou; Huang, Tingxuan; Tang, Hongfeng (Frontiers in Medicine, 2024)
Objective: Individuals with psoriasis face significant physiological and psychological burdens, and their compliance and satisfaction with medication regimens are alarmingly low. In recent years, the comorbidity of psoriasis has become a research focus. This study aims to explore the potential correlation between psoriasis and the non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR). Methods: Data from 17,941 participants of the National Health and Nutrition Examination Survey (NHANES) spanning two intervals, 2003-2006 and 2009-2014, served as the foundation for this analysis. We used weighted logistic regression, stratified analysis, and restricted cubic spline (RCS) curve fitting to validate potential associations between NHHR and psoriasis risk. Results: In this investigation, the analysis of three different models highlighted elevated levels of the NHHR as a consistent risk factor for psoriasis. After adjusting for potential confounders, a positive correlation was observed between NHHR and the prevalence of psoriasis (OR=1.08, 95% CI: 1.01,1.15, P<0.05). Subgroup analysis and interaction tests were conducted to determine if variables such as age, gender, race/ethnicity, education level, smoking status, alcohol consumption, diabetes, coronary heart disease, and stroke impact the association between NHHR and psoriasis. The findings indicated no significant modification of the NHHR-psoriasis link by these factors, as all interaction p-values were above 0.05. The RCS analysis uncovered a nonlinear relationship between psoriasis and the NHHR (P=0.0176). Conclusions: Statistical analysis confirms a significant correlation between the NHHR and the development of psoriasis, suggesting that NHHR may serve as a novel marker for predicting psoriasis risk. This correlation also provides insights for early health management strategies.